Application performances of two greenhouses with new types of backwall in Yangling, China - Sun, Yachen; Wang, Haotian; Zhu, Chenmeng; Lyu, Hongyi; Zhang, Xuanhe; Cao, Yanfei; Li, Jianming; Zou, Zhirong; Bao, Encai (International Journal of Agricultural and Biological Engineering, 2022)
In order to investigate the application performances of the solar greenhouses with new types of backwalls (greenhouse W2, and greenhouse W3) and the ordinary clay brick backwall greenhouse (greenhouse W1), and provide a theoretical basis for the construction of solar greenhouses in Yangling Demonstration Zone, Shaanxi, China, two greenhouses with different new types of backwall were designed. One of the backwall was built with lightweight aggregate concrete block (greenhouse W2) and that of the other one was assembled with a row of sand-filled cement pipes (greenhouse W3). The tested greenhouses were constructed in Yangling Demonstration Zone. Based on the data collected on typical sunny and cloudy days, the indoor temperature, inside wall temperature, and the heat flow of the greenhouses with new types of backwalls were compared with those detected in the ordinary clay brick backwall solar greenhouse, and the tested results were numerically simulated. According to the comparison of the physiological indicators of tomatoes planted in the greenhouses and the construction costs, the greenhouse type with the best practicability was found. The results indicated that: The average air temperature in greenhouses W1, W2, and W3 and outside was 15.1°C, 15.9°C, 17.3°C, and −0.4°C on the night of a sunny day, and the air temperature in W3 was the highest. The average air temperature in greenhouses W1, W2, and W3 and outside were 9.5°C, 13.3°C, 11.0°C, and −5.5°C on the night of a cloudy day, the air temperature in W2 was the highest. In the depth of 0-330 mm from the interface of the backwalls, the walls were obviously affected by the solar radiation, and the temperature changed greatly. The wall temperature on the sunny days exhibited an ascending order of W1, W2, and W3, while on the cloudy days was in the ascending order of W1, W3, and W2. The wall of W3 absorbed the most heat during the daytime and released the most heat at night on a sunny day, while W2 exhibited the second most heat absorption during the daytime, however, it exhibited the highest heat release at night on a cloudy day, which were almost equaled to its heat absorption. Tomatoes in W3 grew well and exhibited the highest yield, and this greenhouse had the lowest construction costs. Comprehensively considering the physiological indicators of tomatoes and the corresponding construction costs of greenhouses, W3 has the best application performance in Yangling Demonstration Zone. Keywords: application performances, solar greenhouse, backwall, temperature DOI: 10.25165/j.ijabe.20221503.6097 Citation: Sun Y C, Wang H T, Zhu C M, Lyu H Y, Zhang X H, Cao Y F, et al. Application performances of two greenhouses with new types of backwall in Yangling, China. Int J Agric & Biol Eng, 2022; 15(3): 62–71.